Plantas medicinales del pueblo achuar : propuesta metodológica para décimo año de EGB. - Unkum Titia, Wasump (2018)
The present research on: Medicinal plants in the Achuar nationality and methodological proposal for the children of the tenth year of basic education, aims to strengthen the treatment of diseases using medicinal plants from the Achuar cosmovisión. These study carried out the following conclusions that were reached: in the Kaiptach community, many medicinal plants used in the treatment of different diseases were identified. And as for the disease of the diarrhea they have identified and defined the causative agents or factors, symptoms and their respective treatment, for the children as for the adults. The different types of ancestral treatments of the diseases must be administered by the healers / specialists who have healing powers, received from their majors through ritual acts of transmission of knowledge, which is practiced from one generation to another. The treatment of diseases with medicinal plants and ritual practices is very practiced in the community until today. Therefore, it is concluded that this type of treatment is in force, and it is important that the parents maintain these good habits of ancestral knowledge, strengthening cultural wealth. And this research met these objectives proposed at the beginning of the work, and will serve as a source of written consultation, so that our methods of transmitting knowledge are no longer oral.